Pengaruh Pembelajaran Role Play Dan Guided Discovery Terhadap Hasil Belajar Matematika Ditinjau Dari Aktivitas Belajar Siswa Kelas VIII Semester Genap SMP Negeri 2 Kartasura Tahun 2015/2016 - DEWI PUJI ASTUTI, ENDAH (2016)
Low ability of student learning outcomes in class VIII SMP Negeri 2 Kartasura , and use learning strategies monotonous with the lack of teaching facilities make researchers interested in conducting research. There are three aims of the research. (1) To knows the influence of Role PlayLearning and Guided Discovery Learning strategy toward student learning outcomes. (2) To knows the influence of learning activity toward student learning outcomes. (3) To knows the interaction between learning strategy and learning activity toward student learning outcomes. The type of the research is quantitatif research with quasi experimental design. The population of the research is all of student eight grade at SMP Negeri 2 Kartasura. The sample of the research is two class that determine using cluster random sampling. The technique of collecting data with test method, quesioner and documentation. The tecnique of analyzing data by using the unbalanced two-way analysis of variance. The finding of the research with α = 5%. (1) there is no influence of learning strategy Role Play and Guided Discovery toward student learning outcomes. (2) there is influence of learning activity toward student learning outcomes. (3) there is no interaction between learning strategy and learning activity toward student learning outcomes.